FDI and the labor share in developing countries: A theory and some evidence - Paul Maarek; Bruno Decreuse (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We address the effects of FDI on the labor share in developing countries. Our theory relies on the impacts of FDI on productive heterogeneity in a frictional labor market. FDI have two opposite effects: a negative force originated by technological advance, and a positive force due to increased labor market competition between firms. We test this theory on aggregate panel data through fixed effects and system-GMM estimations. We find a U-shaped relationship between the labor share in the manufacturing sector and the ratio of FDI stock to GDP. Most countries are stuck in the decreasing part of the curve.
Keywords: E25; F16; F21; 330; FDI; Matching frictions; Firm heterogeneity; Technological advance